A Novel Dendrite‐Free Lithium Metal Anode via Oxygen and Boron Codoped Honeycomb Carbon Skeleton (Small 11/2022). Issue 11 (17th March 2022) - Xie, Yiwen; Zhang, Haiyan; Yu, Jiale; Liu, Zhenjiang; Zhang, Shangshang; Shao, Huaiyu; Cao, Yuliang; Huang, Xifeng; Li, Shengkai
Abstract : Lithium Ion Batteries In article number 2104876, Haiyan Zhang and co‐workers prepare an oxygen and boron co‐doped honeycomb carbon skeleton via soft template and realize a stable Li metal‐based anode. The three‐dimensional carbon structure and abundant lithiophilic oxygen and boron‐containing functional groups reduce the local current density and lead to the homogeneous Li‐ions flux. This strategy is effective in inhibiting the growth of lithium dendrites.